Active galactic nuclei at z ∼ 1.5 – II. Black hole mass estimation by means of broad emission lines. Issue 1 (25th May 2016) - Mejía-Restrepo, J. E.; Trakhtenbrot, B.; Lira, P.; Netzer, H.; Capellupo, D. M.
Abstract: This is the second in a series of papers aiming to test how the mass ( M BH ), accretion rate ( Ṁ ) and spin ( a * ) of supermassive black holes (SMBHs) determine the observed properties of type I active galactic nuclei (AGN). Our project utilizes a sample of 39 unobscured AGN at z ≃ 1.55 observed by Very Large Telescope/X-Shooter, selected to map a large range in M BH and L / L Edd and covers the most prominent UV–optical (broad) emission lines, including Hα, Hβ, Mg ii λ2798 and C iv λ1549. This paper focuses on single-epoch, 'virial' M BH determinations from broad emission lines and examines the implications of different continuum modelling approaches in line width measurements. We find that using a local power-law continuum instead of a physically motivated thin disc continuum leads to only slight underestimation of the full width at half-maximum (FWHM) of the lines and the associated M BH (FWHM). However, the line dispersion σline and associated M BH (σline ) are strongly affected by the continuum placement and provides less reliable mass estimates than FWHM-based methods. Our analysis shows that Hα, Hβ and Mg ii can be safely used for virial M BH estimation. The C iv line, on the other hand, is not reliable in the majority of the cases; this may indicate that the gas emitting this line is not virialized. While Hα and Hβ show very similar line widths, the mean FWHM(Mg ii ) is about 30 per cent narrower than FWHM(Hβ). We confirm several recent suggestions to improve the accuracy in C iv -based mass estimates, relying on other UV emission lines. Such improvements do not reduce the scatter between C iv -based and Balmer-line-based mass estimates.